Design and Simulation of a Solar Thermal Dryer for Fruits. - Amanya, Sylus (Kabale University, 2024)
The write-up presented in this report focused on the design and manufacture of a solar thermal dryer for fruits that dries 5Kg of fruit slices, 5mm thick per batch, and can be used for small-scale farmers that grow fruits in western Uganda following a challenge they face like pests and disease infestation during open sun drying, nutrient loss and among others. The designed dryer aims to improve food security and reduce waste since there will be reduced post-harvest losses allowing people to preserve fruits for longer periods. More so, there will be economic empowerment and income generation as it will necessitate shelf-stable products that can be stored and sold thus generating additional income. The main objective was to design and manufacture a user-friendly solar fruit dryer that utilizes minimal effort and harnesses the power of the sun to dehydrate various fruits into tasty chips. This was guided by three specific objectives i.e. to conceptualize the design of an efficient solar thermal system for drying fruits, optimize the drying efficiency by creating a controlled airflow system, and evaluate the performance of the proposed dryer through simulation. The methods used in carrying out this project included library search, internet search, and brainstorming of different ideas. By reviewing the design parameters of other already established related designs, the conceptual design was formulated and developed in SOLIDWORKS. The design of major components was carried out while others were selected. Steady-state thermal and fluent analyses were performed with the help of the ANSYS workbench 2024 R1 software to study the behavior of the absorber plate, solar collector, and trays.